An approach to manufacturing heat-stable and bloom-resistant chocolate by the combination of oleogel and sweeteners. (October 2022) - Chen, Haiying; Zhou, Peiwen; Song, Chunfang; Jin, Guangyuan; Wei, Lingjun
Abstract: Producing heat-stable, bloom-resistant chocolate is a significant challenge faced by the food industry. This study prepared oleogels using palm oil as a base oil and monoglyceride stearate as an oleogelator, which were introduced into partially substituted cocoa butter (CB) (30% w/w) to manufacture heat-stable, bloom-resistant chocolate. In addition, various healthy sweeteners (maltitol (M), tagatose (T), and palm sap sugar (PS)) were used (corresponding chocolate noted as Choc M100, Choc T5 & T10, and Choc PS25 & PS50, respectively) at different substitution ratios to sucrose. The melting properties and fat blooming behavior were characterized to optimize the suitable recipe for the chocolate. According to the results, Choc PS50 exhibited the required crystal form (β-form), improved the shape retention index (SRI), displayed a higher melting enthalpy ( Δ H m ) and ideal fat bloom-resistance, while showing fewer superficial crystals during temperature cycling (16 h at 20 °C and 8 h at 32 °C for 40 d). Nevertheless, the formulated chocolates exhibited significantly lower hardness due to the reduced CB content. This study provided an approach to manufacturing heat-stable, bloom-resistant chocolate. Highlights: Positive synergy of oleogel and palm sap sugar occurred in improving the heat stability and bloom resistance of chocolate. All the chocolate samples exhibited the ideal crystal forms (β-form). Choc PS50 became soft and kept their shape at 35 °C, even still could see their original shape at 40 °C. Choc PS50 demonstrated the lowest WI and the minimum white spots during the 40 days' temperature cycling.